Komposisi Karawitan “Maha Aksa” - I Made Andika Candra Wigraha; Ni Ketut Dewi Yulianti; I Nyoman Mariyana (Journal of Music Science, Technology, and Industry, 2023)
Purpose: this karawitan artwork is to transform the idea obtained from the fly’s vision system into "Maha Aksa karawitan" artwork. Meanwhile, this paper is also intended to describe the values contained in "Maha Aksa karawitan artwork." Methods: the creating process of “Maha Aksa" artwork uses the method by Alma M. Hawkins, which consists of 3 stages, namely Exploration, Improvisation, and Forming. This artwork uses “Asta Wirat Bhumi” gamelan as an expression media. Result and Discussion: “Gamelan Asta Wirat Bhumi” was created from exploration and combination of 3 Balinese gamelan elements, namely “Jegog, Balaganjur, and Selonding gamelan.” The new karawitan artwork "Maha Aksa" is an educational media inspired by the sighting system of flies with compound eyes that have a perspective on the speed of movement. Implication: the values contained in the new karawitan artwork "Maha Aksa" are the story values (moral values) and formal values (artistic values).